Comprehensive analysis of adverse events associated with onasemnogene abeparvovec (Zolgensma) in spinal muscular atrophy patients: insights from FAERS database - Zhang, Wenwen; Yin, Yizhen; Yang, Dan; Liu, Mengyuan; Ye, Caixia; Yan, Ruiling; Li, Ruiman (Frontiers in Pharmacology, 2025)
Onasemnogene Abeparvovec (Zolgensma) is a gene therapy for the treatment of Spinal Muscular Atrophy (SMA) with improved motor neuron function and the potential for a singular treatment. Information on its adverse drug reactions is mainly from clinical trials and real-world studies with extensive sample sizes are lacking. In this study, we analyzed the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database to assess the drug safety profile of Zolgensma. A total of 1951 adverse event reports associated with onasemnogene abeparvovec (Zolgensma), containing 778 import important medical event (IME) signals, were identified from the FAERS database, and multiple disproportionate analysis algorithms were used to determine the significance of these adverse events. This study identified 281 onasemnogene abeparvovec-related adverse events (AEs), including some significant adverse events not mentioned in the product labelling. Elevated liver enzymes, fever, vomiting, and thrombocytopenia were the most common adverse reactions. Most adverse events manifested within the initial month of onasemnogene abeparvovec use, especially the first 8 days, but some may still occur after 1 year of treatment. Sex-specific scrutiny revealed differing risk levels for adverse events among women and men. Thrombocytopenia and thrombotic microangiopathy are more common in patients weighing ≥8.5 kg, and changes in renal function need to be closely monitored if thrombotic microangiopathy occurs. The above findings provide valuable insights into optimizing the utilization of onasemnogene abeparvovec, improving its effectiveness, and minimizing potential side effects, thereby greatly facilitating its practical application in clinical settings.